Hand hygiene and catheter related bacteraemia rates in ICU patients in Latvia during five years, before and after interventions - Melbarde-Kelmere, Agita; Dumpis, Uga (International Journal of Infection Control, 2016)
Implementation of a procedure of evidence-based measures resulted in reduced incidence of catheter related bacteraemia from 13.3 to 2.1 cases per 1000 bed days. This improved the results of patient treatment, and shortened the length of hospitalisation. Correct personnel hand hygiene is one of the infection control measures. The results obtained during the study showed that at the beginning hand hygiene compliance indicators were very low (8%), but after implementing targeted measures, these results improved.